Development of Student Work Sheet Based Discovery Learning on The Material Human Respiratory System Class XI Madrasah Aliyah - Tanjung, Siti Aisyah; Khairuna, Khairuna; Afinni Dwi Jayanti, Ummi Nur (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to develop Discovery Learning Based Worksheets and to determine the level of validity, practicality and effectiveness. This study uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects were class XI MIA at MAS Al-Washliyah 22 Tembung, which consisted of 34 people. The research instrument was an analysis of teacher needs, validation sheets, educator response questionnaires and student questionnaires. Based on the results of research in terms of validity, material experts get a score of 100% in the "Very Valid" category, media experts get a score of 81.05% in the "Valid" category. Meanwhile, in terms of practicality, from the results of the educator's response, an average response of 95% was classified as "Very Practical". In the results of the assessment of students have an average proportion of 90.47% with the criterion "Very Interesting". In terms of effectiveness, the pretest results averaged 61.18 while the posttest results averaged 74.26. With an n-gain value obtained of 0.34 which is the "Effective" criterion. Thus, the LKPD based on Discovery Learning that has been developed is declared valid, effective, and practical to use, and can increase activeness in solving problems. 34 which is the "Effective" criterion. Thus, the LKPD based on Discovery Learning that has been developed is declared valid, effective, and practical to use, and can increase activeness in solving problems. 34 which is the "Effective" criterion. Thus, the LKPD based on Discovery Learning that has been developed is declared valid, effective, and practical to use, and can increase activeness in solving problems.